2021
DOI: 10.1111/xen.12693
|View full text |Cite
|
Sign up to set email alerts
|

Xenotransplantation of neonatal porcine bone marrow‐derived mesenchymal stem cells improves murine hind limb ischemia through lymphangiogenesis and angiogenesis

Abstract: Background The clinical utility of stem cell therapy for peripheral artery disease has not been fully discussed, and one obstacle is limited donor supplies. In this study, we attempted to rescue mouse ischemic hind limb by xenotransplantation of neonatal porcine bone marrow‐derived mesenchymal stem cells (npBM‐MSCs). Methods Neonatal porcine bone marrow‐derived mesenchymal stem cells were transplanted to ischemic hind limbs of male C57BL/6J mice (npBM‐MSCs group). Mice with syngeneic transplantation of mouse B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…We previously clarified that npBM-MSCs were characterized by super-rapid growth, a small size, and a robust proliferation profile 36 and elucidated that xenotransplantation of npBM-MSCs improved murine hind limb ischemia through angiogenesis and lymphangiogenesis. 22 Therefore, the promotion of neonatal porcine granulation. 37 TGF-β expression was decreased in a diabetic ulcer animal model, 38 and inhibition of this cytokine activates inflammatory cells, delaying the proliferation phase of the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously clarified that npBM-MSCs were characterized by super-rapid growth, a small size, and a robust proliferation profile 36 and elucidated that xenotransplantation of npBM-MSCs improved murine hind limb ischemia through angiogenesis and lymphangiogenesis. 22 Therefore, the promotion of neonatal porcine granulation. 37 TGF-β expression was decreased in a diabetic ulcer animal model, 38 and inhibition of this cytokine activates inflammatory cells, delaying the proliferation phase of the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we promote the assessments of neonatal pig as a suitable donor for clinical usage. We previously clarified that npBM‐MSCs were characterized by super‐rapid growth, a small size, and a robust proliferation profile 36 and elucidated that xenotransplantation of npBM‐MSCs improved murine hind limb ischemia through angiogenesis and lymphangiogenesis 22 . Therefore, the promotion of neonatal porcine MSCs is considered as an excellent strategy for future xenotransplantation in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently, we demonstrated that the porcine-derived MSCs improved critical ischemic limb disease in rat model more efficiently compared with human MSCs. 4 On the other hand, since porcine MSC is xenogeneic against human, the implanted MSCs could be eliminated by the xenogeneic rejection. antigens as efficiently as human MSCs do.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently, we demonstrated that the porcine bone marrowderived MSC could more effectively improve critical ischemic limb disease in rat model compared with human MSCs. 4 Even porcine bone marrow-derived MSC improved the ischemic limb disease in rat model, porcine cells present alpha-Gal which could cause xenogeneic rejection. Elimination of alpha-Gal might improve the efficacy of porcine bone marrow-derived MSC by mitigating xenogeneic rejection of implanted MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, people turn to utilize the xenograft of porcine MSCs. Yamada et al [ 79 ] proposed that xenotransplantation of porcine bone marrow MSCs contributed to the improvement of mouse hind limb ischemia through both angiogenesis and especially lymphangiogenesis, showing the potential of being an alternative source for stem cell therapy ( Table 1 ). Nevertheless, a lack of direct evidence that confirmed the incorporation of MSCs into lymphangiogenesis is flawed, which means we cannot rule out the disturbance of the paracrine effect.…”
Section: Stem/progenitor Cells In Postnatal Lymphangiogenesismentioning
confidence: 99%